2018
DOI: 10.1136/heartjnl-2017-312299
|View full text |Cite
|
Sign up to set email alerts
|

Short-term risk of cardiovascular readmission following a hypertensive disorder of pregnancy

Abstract: Women with HDP had twice the risk of CV readmission within 3 years of delivery, with higher rates among AA women. More work is needed to explore preventive strategies for HDP-associated events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
2
26
0
2
Order By: Relevance
“…GH was associated with an 18% increase in 5‐year CVD risk; however, the significance was attenuated after adjustment. In addition, women with HDP have been found to have a roughly 2.4‐fold greater adjusted odds of hospitalization due to cardiovascular causes within 3 years of delivery compared with those without HDP 57. Another study examining hospitalizations due to CVD events showed that women with GH, mild preeclampsia, and severe preeclampsia had 2.8‐fold, 2.2‐fold, and 3.3‐fold increased risk of CVD events, respectively, over a mean follow‐up of 7.8 years 45…”
Section: Hdp and Early To Midterm Risk Of Maternal Cvdmentioning
confidence: 99%
“…GH was associated with an 18% increase in 5‐year CVD risk; however, the significance was attenuated after adjustment. In addition, women with HDP have been found to have a roughly 2.4‐fold greater adjusted odds of hospitalization due to cardiovascular causes within 3 years of delivery compared with those without HDP 57. Another study examining hospitalizations due to CVD events showed that women with GH, mild preeclampsia, and severe preeclampsia had 2.8‐fold, 2.2‐fold, and 3.3‐fold increased risk of CVD events, respectively, over a mean follow‐up of 7.8 years 45…”
Section: Hdp and Early To Midterm Risk Of Maternal Cvdmentioning
confidence: 99%
“…demonstrated that women with a history of HDP had a significantly higher extrapolated 10‐ and 30‐year cardiovascular event risk compared with normotensive women. Furthermore, women with prior HDP have been found to have a roughly 2.4‐fold greater adjusted odds of hospitalization due to cardiovascular causes within 3 years of delivery compared with normotensive women …”
Section: Placental Syndromesmentioning
confidence: 99%
“…Pre-eclampsia and hypertension have long been associated with cardiovascular disease in later life16 17; recent data suggest an increased risk of AMI associated with pre-eclampsia which is particularly marked in the puerperium 18. Mulla et al showed in their retrospective cohort study that 16% of cases of AMI in pregnancy were associated with pre-eclampsia19 Hypertension is also strongly associated with AMI and pregnancy as it may exacerbate damage to blood vessels that have already undergone adverse remodelling due to the haemodynamic stress of pregnancy and endothelial activation.…”
Section: Risk Factors For Ihd In Pregnancymentioning
confidence: 99%